Kesesuaian Model Hidrograf Satuan Sintetik (HSS) Berdasarkan Karakteristik Daerah Aliran Sungai Di Wilayah Sungai Indragiri-Akuaman - Tri Setia Budi; Andy Hendri; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Synthetic Unit Hydrograph is a simple and practical method to analyze the design flood discharge of a watershed. This method can be used for watershed do not have the tools of Automatic Water Level Recorder (AWLR) and discharge recording.The method can analyze only the flood discharge based on the basin characteristics. Antokan, Andaman, Tiku, Gasang Gadang’s basin are some watershed flood discharge to be analyzed in this study. The characteristics of the sixth watershed obtained using Digital Elevaltion Digital Model (DEM) data and then be processed using Geographic Information System (GIS). GIS will produce the output of the watershed characteristic data needed to calculate the Syntethic Unit Hydrograph flood discharge, there were Snyder, SCS, Gamma I, and Nakayasu’s methodes. The method will be compared to get the most optimum method and can be applied in the watershed of reviews with HDRO close to 1 mm and a volume error of less than 5%. In the case study can be viewed unit hydrograph can be applied to the Antokan, Andaman, Tiku, Gasang Gadang’s watershed is SCS and Nakayasu’s method with HDRO obtained 1 mm and volum error less than 5%.Keywords: Basin characteristics, GIS, Synthetic Unit Hydrograph